A case of diaphragmatic rupture in a Criollo pony - Khairuddin, Nurul Hayah; Roslim, Noorashimah; Ahmad Affandi, Syahirah; Lau, Seng Fong; Lim, Sue Yee (Universiti Putra Malaysia Press, 2017)
This report describes a case of diaphragmatic rupture with migration of small and large intestines into the thoracic cavity of an 18-year-old Criollo pony. The pony was initially presented to the University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM), with mild colic and increased respiratory effort. A diagnosis of diaphragmatic rupture was made based on thoracic auscultation, radiographic and ultrasonographic findings. Due to financial constraints, surgical management was not an option and so the pony was managed medically. The pony was diagnosed with diaphragmatic rupture and concurrent bronchopneumonia and was observed closely. Mild colic was treated with analgesics while dyspnoea was managed symptomatically with bronchodilators and antibiotics. The pony remained clinically stable for more than eight (8) weeks. However, another episode of colic lead to a deterioration in its clinical condition and subsequent death. Post-mortem findings revealed migration of loops of small intestines and part of the large colon into the thoracic cavity. There was a linear tear (estimated to be about 15cm in length) in the right dorsal segment of the diaphragm at the border of the muscular and fibrous portion, which confirmed our clinical and diagnostic imaging findings of diaphragmatic rupture that had caused the pony to suffer from colic and dyspnoea.